2014
DOI: 10.1016/j.tcs.2014.04.032
|View full text |Cite
|
Sign up to set email alerts
|

2-Connecting outerplanar graphs without blowing up the pathwidth

Abstract: Given a connected outerplanar graph G of pathwidth p, we give an algorithm to add edges to G to get a supergraph of G, which is 2-vertex-connected, outerplanar and of pathwidth O(p). This settles an open problem raised by Biedl [1], in the context of computing minimum height planar straight line drawings of outerplanar graphs, with their vertices placed on a two dimensional grid. In conjunction with the result of this paper, the constant factor approximation algorithm for this problem obtained by Biedl [1] for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 11 publications
0
11
0
Order By: Relevance
“…2(left). Hence it requires width at least 1 3 2 d by the previous lemma and Γ H cannot be smaller. One can easily show that H requires at least 4 rows in any straight-line drawing.…”
Section: Theoremmentioning
confidence: 92%
See 1 more Smart Citation
“…2(left). Hence it requires width at least 1 3 2 d by the previous lemma and Γ H cannot be smaller. One can easily show that H requires at least 4 rows in any straight-line drawing.…”
Section: Theoremmentioning
confidence: 92%
“…The height is thus measured by the number of rows, i.e., horizontal lines with integer y-coordinates that intersect the drawing. 1 Drawings in this paper are required to be grid-drawings, with some exceptions for ease of description that will be pointed out as they occur.…”
Section: Preliminariesmentioning
confidence: 99%
“…In contrast, the network topology, such as acyclicity or planarity, as a constraint to be preserved has received little attention in the context of complementing a graph; see for example [14]. See also [20,21] for other augmentation problems in outerplanar graphs, where the objective is to add edges in order to achieve a prescribed connectivity.…”
Section: Introductionmentioning
confidence: 99%
“…(For if so, then all outer-planar graphs can be drawn with height O(pw(G)).) This question was answered in the affirmative by Babu et al [1], who showed that any outer-planar graph G can be made into a 2-connected outer-planar graph G with pw(G ) ≤ 16pw(G) + 15.…”
Section: Introductionmentioning
confidence: 99%
“…Research was supported by NSERC and done while visiting Universität Salzburg. Many thanks to Jasine Babu for sharing her manuscript of what later became [1], and the referees of an earlier version of this paper for helpful comments.…”
Section: Introductionmentioning
confidence: 99%